The effect of audiovisual tape self-confrontation on the self-concept of high-anxiety twelfth-grade students within a client-centered counseling situation. - Crowder, Thomas H., Jr. (University of Ottawa (Canada), 1978)
The problem of this study was to determine the effect of varying degrees of intensity of audiovisual tape self-confrontation upon the self-concept of high anxiety twelfth-grade students in a group counseling situation under client-centered conditions. The general hypothesis was that, if audiovisual self-confrontation is used in client-centered group counseling, then significantly higher scores will result on a measure of self-concept than if such confrontation is not used. The study was based upon the premise that audiovisual self-confrontation represents a unique adjunct to the techniques of client-centered therapy in providing to the client an objective view of his own behavior as well as the reactions of others to his behavior. By providing this view, the confrontation is supportive of the self-perception purpose of therapeutic techniques. It tests the client-centered theory assertions that (1) one of the objectives of therapy is to help the client differentiate and discriminate the objects of his feelings and perceptions, including his self, thereby bringing about a more positive self-concept, and (2) if incongruence exists, a sudden or obvious demonstration of the incongruence may result in a deteriorated self-concept. In order to test the effect of audiovisual self-confrontation, high anxiety twelfth-grade students were assigned randomly to two groups of six students in each of five high schools. In each group, students were designated randomly, two for focused self-confrontation (with discussion), two for unfocused self-confrontation (without discussion), and two for no self-confrontation as control. Following a twenty-five-minute client-centered group counseling session (with self-confrontation for designated students) each week over a six-week period, students were tested on the self-concept variable. The results did not support the hypothesis that audiovisual self-confrontation would enhance the self-concept. There was no statistically significant difference between the self-concept scores of the focused, unfocused, and control groups of students. Therefore, both Hypothesis 1 and Hypothesis 2 were rejected. The results of the study did indicate that, for the students involved under the given conditions, audio-visual self-confrontation was not effective as an adjunct in the implementation of client-centered therapy.
Keywords: Education, Guidance and Counseling.